2009
DOI: 10.1590/s1415-47572009005000077
|View full text |Cite
|
Sign up to set email alerts
|

Parentage test in broad-snouted caimans (Caiman latirostris, Crocodylidae) using microsatellite DNA

Abstract: In this study, microsatellite markers, developed for Alligator mississipiensis and Caiman latirostris, were used to assess parentage among individuals from the captive colony of Caiman latirostris at the University of São Paulo, in Piracicaba, São Paulo, Brazil. Many of the females in the colony were full siblings, which made maternal identification difficult due to genotypic similarity. Even so, the most likely mother could be identified unambiguously among offspring in most of the clutches studied. Two non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
0
9
0
1
Order By: Relevance
“…This can be attributed to the possibility of the presence of eggs from different females in the nest, in agreement to observations of Larriera et al (2002) in this species. In addition, Zucoloto et al (2009) found in a study conducted in six C. latirostris clutches that two females who were assigned by genetic analysis as mothers each one to one nest were not the same as those indicated by maternal behavior. The authors explained the display of maternal behavior by nonmothers as a behavioral malfunction caused by the captive environment or species social adaptation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This can be attributed to the possibility of the presence of eggs from different females in the nest, in agreement to observations of Larriera et al (2002) in this species. In addition, Zucoloto et al (2009) found in a study conducted in six C. latirostris clutches that two females who were assigned by genetic analysis as mothers each one to one nest were not the same as those indicated by maternal behavior. The authors explained the display of maternal behavior by nonmothers as a behavioral malfunction caused by the captive environment or species social adaptation.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, microsatellite markers are useful in helping to understand mating patterns of C. latirostris due to the possibility of its use as fingerprints. Zucoloto et al (2009) applied SSR analysis to assess parentage among individuals from a captive colony of C. latirostris. In relation to mating system analyses in the wild, preliminary results obtained in our laboratory using SSRs in paternity analysis found evidence of multipaternity in one of four families analyzed (Amavet et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst nest protecting behaviour often assumes the female is also the biological dam, and indeed was found to be the case in Davis et al (2001) and Lance et al (2009), mis-assignments have also been reported. Using a captive population of Caiman latirostris with a documented Studbook pedigree (Verdade & Andrade, 2003), Zucoloto et al (2009) found that two out of six nests were being protected by a non-biological female. In both of these instances, the nest-protecting female was heavier in body mass than the biological female (L.M.…”
Section: Discussionmentioning
confidence: 99%
“…site fidelity; Lance et al, 2009, Zajdel et al, 2019 as that information is not available. Alternatively, the nest-protective behaviour observed may have been misinterpreted as 1) protection of their normal, non-reproductive niche basking area, 2) "joint care" or "alloprotection" behaviour; 3) a (programmed) response to human presence, or 4) a social (mal)adaptation of the captive environment (Zucoloto et al, 2009). Milián-García et al ( 2016) also describe potential alloprotection in captive Crocodylus rhombifer but the protecting female was identified before oviposition and therefore this behaviour may have been independent of reproductive effort.…”
Section: Discussionmentioning
confidence: 99%
“…Nestas duas décadas da história do programa, o conhecimento da biologia e manejo deste crocodiliano aumentou consideravelmente devido a pesquisas em biologia reprodutiva LARSEN et al, 1992;VERDADE et al, 1992a, 1992bVERDADE, 1995;SARKIS, 1998;VERDADE, 2001b;VERDADE et al, 2003;LARRIERA et al, 2004;, comportamento social (VERDADE, , 1999PIFFER;, comportamento de termorregulação (VERDADE et al, 1994;FINCATTI;BASSETTI et al, 2005), manejo alimentar (VERDADE et al, 1992c, SARKIS-GONÇALVES;SARKIS-GONÇALVES et al 2002), aspectos sanitários (RAMOS et al, 1992;GARCIA et al, 1993), morfometria VERDADE, 2003;, biologia molecular (ZUCOLOTO; VERDADE; VILLELA et al, 2008;ZUCOLOTO et al, 2009) e uso do espaço . Além disso,…”
Section: Introdução Geralunclassified